Total nitrogen and humic substances in aggregates of soils with onion crops under no-tillage and conventional tillage systems - Dos Santos, Luiz Henrique; Loss, Arcângelo; Lourenzi, Cledimar Rogério; Souza, Monique; Gonzatto, Rogério; Kurtz, Claudinei; Brunetto, Gustavo; Comin, Jucinei José (Universidad Pedagógica y Tecnológica de Colombia, 2019)
1 recurso en línea (páginas 166-174).